THE IMPLICATIONS OF FEMALE STUDENTS' INVOLVEMENT IN CAMPUS ORGANIZATIONS ON CLASSROOM LEARNING QUALITY: A CASE STUDY AT STIT MADANI YOGYAKARTA - Keysha Alea Savinka; Hafidza Azzahra Qurrota Aini; Eko Ngabdul Shodikin (Proceeding of International Conference of Islamic Education, 2025)
Female students' involvement in campus organizations often poses a challenge in maintaining a balance between academic and non-academic activities. On the other hand, campus organizations also have great potential in developing soft skills that support learning. The purpose of this study is to analyze the implications of female students' involvement in campus organizations on classroom learning quality, particularly at STIT Madani Yogyakarta. This study employs a qualitative method with a case study approach. Data was collected through in-depth interviews with organization leaders, academic advisors, and female students involved in the organization, supported by observations. The results of the study indicate that involvement in organizations has a positive impact on learning productivity, self-confidence, soft skills (communication, leadership, and time management), and increased self-confidence. However, role imbalance also causes stress, fatigue, and a decline in academic focus. Time management skills, environmental support, and self-awareness are some of the components that influence the balance between academic and organizational activities. The use of time management applications, setting priorities, daily planning, and selecting organizational activities aligned with personal principles are some strategies employed by female students. This study suggests that organizational involvement can be an effective learning tool when implemented with suitable strategies.